2001
DOI: 10.1111/0045-3609.00120
|View full text |Cite
|
Sign up to set email alerts
|

From Responsible Management to Responsible Organizations: The Democratic Principle for Managing Organizational Ethics

Abstract: An increasing number of organizations have adopted formal ethics programs. Almost all of these programs are institutionalized at a corporate level and based on communication with representatives and on hierarchical regulations. Sociotechnical theory suggests the use of a participative approach for managing ethics in an organization. In this approach, employees and other stakeholders are directly involved in setting the norms, or specifying the corporate norms in their own area of responsibility (the democratic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…The findings illustrate that the employees were intrinsically motivated to contribute to the social cause (Hilliard 2013, p. 372). Verkerk et al (2001) have shown that a democratic approach to management in which there is room for participatory processes involving employees has two positive impacts on the implementation of ethics programmes by employees. First, the democratic approach leads to the internalisation of ethical values by employees.…”
Section: Responsible Management Learning and Responsible Management Cmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings illustrate that the employees were intrinsically motivated to contribute to the social cause (Hilliard 2013, p. 372). Verkerk et al (2001) have shown that a democratic approach to management in which there is room for participatory processes involving employees has two positive impacts on the implementation of ethics programmes by employees. First, the democratic approach leads to the internalisation of ethical values by employees.…”
Section: Responsible Management Learning and Responsible Management Cmentioning
confidence: 99%
“…The rise of environmental sustainability as an area of competitive advantage has triggered management scholars to identify competences and capabilities of managers and businesses that enhance environmental performance (van Kleef and Roome 2007;Hesselbarth and Schaltegger 2014). One area of research that studies the competences of managers for sustainability, responsibility and ethics (SRE) is the field of responsible management (Verkerk et al 2001;Hilliard 2013;Laasch and Conaway 2015). The responsible management literature has made significant contributions to the education sciences by analysing the roles of universities and business schools in the development of responsible management competences in education settings (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, as outlined in the previous section, our review of IW and (ir)responsible management highlights that most research tends to focus on the adoption of supposedly responsible practices, ideas, standards, or structures in a relatively symbolic way. By that we mean, instead of empirically exploring the actual impact of such adoption in the day-to-day lives of different actors, including institutional workers, research focuses on the (relatively superficial) organizational adoption of these practices, ideas, standards, or structures (Verkerk et al, 2001). This is partly due to the fact that adoption in this sense is much easier to capture, measure and operationalize in data collection and analysis, than fuzzier, often less visible and measurable, impact on the ground (e.g.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…While this may sound relatively trivial, extant research has shown that the wider societal frameworks in which businesses and managers operate are, arguably, configured to induce irresponsibility (Ennals, 2014). An interesting question therefore arises in responsible management research (Verkerk et al, 2001): How might managers, activists, consumers, workers and others push firms to engage in responsible management despite these structural and cultural barriers?…”
Section: Introductionmentioning
confidence: 99%